Investigation of the structure of heat-resistant alloys under direct laser cultivation - D. A. Baranov (Литьë и металлургия, 2023)
In this work, the following studies were carried out: the structure of the starting materials (metal‑powder composition) of heat‑resistant nickel alloys EP648 and VJ159; sphericity, fluidity and bulk density of powder particles from heat‑resistant nickel alloys EP648 and VJ159; elemental (chemical) composition of powder particles of heat‑resistant nickel alloys EP648 and VJ159; the effect of technological and energy parameters of laser radiation on defect formation (pore) in manufactured (grown) blanks (samples); structure formation of manufactured samples from heat‑resistant nickel alloys EP648 and VJ159.Based on the results obtained, the following were determined: the causes of the formation of satellites on the particle surface of metal‑powder compositions made of heat‑resistant nickel alloys EP648 and VJ159; the causes of the formation of a "layered" and fine‑grained multidirectional structure of manufactured (grown) blanks; the regularities of the effect of the crystallization rate of the melt bath on the total area of defects (pores) in the metal.